The role of vocabulary knowledge in L2 speaking and writing abilities of Thai EFL undergraduates - Apisak Sukying (Penerbit Universiti Kebangsaan Malaysia, 2025)
Research has shown the essential role of vocabulary knowledge in achieving second language (L2) proficiency. This study investigates the nature of vocabulary knowledge and its role in L2 speaking and writing abilities. Five vocabulary knowledge tests were administered to 63 English major students who completed speaking and writing tasks to assess their productive language abilities. Speaking and writing tasks were rated by two trained, experienced raters. Results showed that vocabulary is incremental and multifaceted, with foundational knowledge acquired earlier and more thoroughly than the more complex aspects. This progression highlights the sequential nature of vocabulary learning, where basic recognition and understanding establish the foundation for deeper comprehension and active vocabulary use. Regression analyses confirmed that vocabulary is cumulative and integrative, with each layer of understanding enhancing language proficiency. Specifically, the form and meaning of vocabulary, measured by the VLT and WAT, account for 28.8% of the variance in L2 speaking ability, while depth of vocabulary knowledge, measured by the PVLT and WAT, significantly predicted 71.2% of the variance in L2 writing performance. These results highlight the critical role of vocabulary knowledge in productive language skills and that different aspects of vocabulary knowledge contribute differently to language proficiency. Future research should focus on the need for targeted vocabulary assessments and instruction that align closely with the specific demands of language learning and proficiency development.